Water footprint assessment of sheep and goat production in the agro-pastoral production system in the region of Sidi Bouzid in Central Tunisia - Ibidhi R.; Ben Salem H. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
There is an increasing concern on the continuous and rapid decrease of water availability across the whole territory particularly in central and southern Tunisia. This constraint is adversely affecting livestock production and the sustainability of different production systems. Agriculture is a major water-consuming sector. Small ruminants’ production is the main source of income of most of households in the region of Sidi Bouzid (semi-arid region in Central Tunisia). However, water scarcity is threatening this sector. This study aims to determine water footprint (WF) in the community of Zoghmar in Sidi Bouzid and to assess water use in sheep and goat farming, using a water footprint method compliant with life cycle assessment. A distinction is made between green, blue and grey water footprint, to make a comprehensive and complete overview of freshwater consumption and pollution. Data have been generated from a survey performed on a wide range of farms in this community. Three main factors driving the WF of meat: feed conversion efficiency (feed amount per unit of meat produced), diet composition and feed origin. Sheep and goat were raised under the agro-pastoral system. This study shows that the average WF of sheep meat is 6222 liter/kg of carcass for which 94% green, 5% blue and 1% grey. However, WF of goat meat averaged 4521 liter/kg of carcass. Proportions of water footprint categories are equal to those obtained with sheep. It is concluded that goat meat production is less water demanding than sheep confirming the common opinion that goat is better adapted to harsh conditions prevailing in arid and semi-arid region than sheep. Moreover, the water footprint of meat is determined mostly on the basis of feeds distributed to the animals, therefore the more low WF feeds, like cactus cladodes, are included in livestock’s diets the lower WF of meat would be recorded.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)